Rectus sheath haematoma complicating dengue haemorrhagic fever-a case report - Kaur, Harharpreet; Girgila, Kawalinder (International Journal of Research in Medical Sciences, 2016)
Dengue hemorrhagic fever manifests in various forms, ranging from petechial skin hemorrhages to life threatening hemorrhages. However it is very rare to have muscle hematomas in this condition. We report a case of spontaneous Rectus sheath hematoma complicating dengue hemorrhagic fever. Our patient was a 55 year old female positive for NS1antigen and anti-dengue IgM. She had thrombocytopenia with platelet counts as low as 12000 in the beginning. There was evidence of plasma leakage and acute dyspnoea during the course of illness. On the 5th day though the platelet count had recovered she developed haematoma in the left rectus sheath which was diagnosed on ultrasound and aspirated leading to relief of symptoms. This complication needs to be recognized so that it can be treated early.